Taxis in Text Structure (Based on B. Pasternak’s Letters from Tula) - Grudeva, Elena V.; Solovyova, Svetlana A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This article is devoted to the problem of analysing the taxis as a text category in the structure of a consistent montage text. The research refers to Letters from Tula (1918), a novel by B. Pasternak. The choice of the text is due to the specifics of its structure. In a montage text, the functional-semantic category of the taxis reflects the author’s idea of the temporal correlation of actions within the framework of an integral period, a temporal frame. Its boundaries are determined by the perceiver. The main methods of linguistic analysis in the article are the descriptive, analytical, and interpretive. The connection between the taxis category and the idea of a semantic plurality of situations appears in the structure of the montage text. Their immersion in a single temporal frame and the system of syntactic means and connections allows them to overcome the simultaneity of the text. Special attention is paid to the system of syntactic means of taxis implementation. This approach makes it possible to reveal the features of the spatio-temporal organisation of the text and discover the principles of compatibility of the components of the text, and their conditionality. The system of grammatical means reflects the conjugation of actions and the intentionality of taxis meanings. In the structure of the text, taxis relations arise between juxtaposed and distantly located fragments of the text connected only by the framework of a common period. Simultaneity becomes the predominant type of the relationship. The system of grammatical means of taxis organisation made up by the unity of aspectual semantics, the parallelism of syntactic structures, and various types of syntactic repetitions becomes a factor that makes it possible to combine parallel developing thematic lines and different ways of narration in the text to show the process of perceptual activity, drawing the reader’s attention to several simultaneously comprehended events as an integrated fragment of reality and stabilising the space of the montage text. The connection between the taxis and the subject’s point of view organises the connections between the subjective and the objective, the figurative and the logical and strengthens the intentionality of taxis semantics, one of whose functions is the organisation of the reading strategy.